Potential benefit of MRI-guided IMRT for flank irradiation in pediatric patients with Wilms' tumor. (1st February 2019) - Guerreiro, F.; Seravalli, E.; Janssens, G. O.; van den Heuvel-Eibrink, M. M.; Lagendijk, J. J. W; Raaymakers, B. W.
Abstract: Purpose/Objective: Flank irradiation for Wilms' tumor (WT) is currently performed at our institute using a cone-beam computed tomography-guided volumetric modulated arc (VMATCBCT ) workflow. By adding real-time magnetic resonance imaging (MRI) guidance to the treatment, safety margins could be reduced. The study purpose was to quantify the potential reduction of the planning target volume (PTV) margin and its dosimetric impact when using an MRI-guided intensity modulated radiation therapy (IMRTMRI ) workflow compared to the VMATCBCT workflow. Material/Methods: 4D-CT, MRI and CBCT scans acquired during preparation and treatment of 15 patients, were used to estimate both geometric, motion and patient set-up systematic (∑) and random (σ) errors for VMATCBCT and IMRTMRI workflows. The mean PTV (PTVmean ) expansion was calculated using the van Herk formula. Treatment plans were generated using five margin scenarios (PTVmean ± 0, 1 and 2 mm). Furthermore, the IMRTMRI plans were optimized with a 1.5T transverse magnetic field turned-on to realistically model an MRI-guided treatment. Plans were evaluated using dose-volume statistics ( p <.01, Wilcoxon). Results: Analysis of ∑ and σ errors resulted in a PTVmean of 5 mm for the VMATCBCT and 3 mm for the IMRTMRI workflows in each orthogonal direction. Target coverage was unaffected by the margin decrease with a mean V95% =100% for all margin scenarios. For the PTVmean, an average reduction of the mean dose to the organs at risk (OARs) was achieved with IMRTMRI compared to VMATCBCT : 3.4 ± 2.4% ( p <.01) for the kidney, 3.4 ± 2.1% ( p <.01) for the liver, 2.8 ± 3.0% ( p <.01) for the spleen and 4.9 ± 3.8% ( p <.01) for the pancreas, respectively. Conclusions: Imaging data in children with WT demonstrated that the PTV margin could be reduced isotropically down to 2 mm when using the IMRTMRI compared to the VMATCBCT workflow. The former results in a dose reduction to the OARs while maintaining target coverage.